A student-run peer-reviewed journal: an educational tool for students in the health sciences - Deonandan, Raywat; Patel, Premal; Winterbottom, Robyn (Université d'Ottawa | University of Ottawa, 2012)
Students at the University of Ottawa, many of whom were targeting a career in medicine, were surveyed to determine their attitudes and expectations regarding a new student-run peer-reviewed journal for the health sciences. A number of students reported that the existence of the journal would make them more likely to take a class with a written component, while a majority would work harder on that assignment. Those intending to pursue postgraduate or professional studies were most likely to recognize the value to their careers of having a publication history. We argue that student-run medical communication endeavors such as this are beneficial both for enhancing student careers and for contributing to a more thorough educational experience.
Keywords: journal; literacy; publication; student; undergraduate; education